(3CSFdI hCLhHI aj GdCMGOjK GdVYjaIs - (3YHO GdSdGe Hf YHO Gddg Hf GdNVQ Hf eMeO, eLO GdOjf CHh GdHQcGJ GHf JjejI GdMQGfj,J (B652 (3g` s ((3YHO Gddg Hf YHO GdhGMO Hf YHO GddWja Hf YHO GdSdGe GdYHGSi s)
(3ChdgG (B:s
(3eG jbhdg GdTjN Jbi GdOjf ajeG jQhi Yf GdfHi UdiGddg Ydjg hSde Yf Gddg YR hLd bGd (B" (3eG hSYfi SeGFi hdG CQVi hdcf hSYfi bdH YHOi GdeDef (B" s
(3BNQgG (B:s
(3eG jQhhg Yf GdfHi Udi Gddg Ydjg hSde (B:" (3ef CSQL SQGLkG ai eSLO de JRd GdedGFcI hMedI GdYQT Pdc GdSQGL gPG dG CYQa dg ESfGOkG Yf GdfHi Udi Gddg Ydjg hSde JeJ GdfHPg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B13s
(3GdfSNI HgG MhGTs
(3HgG Jedc HGSe YHO Gddg Hf YHO GdhGMO Hf YHO GddWja Hf TYjH Hf YHO GdSdGe hjQLY JGQjNgG Edi SfI (B1294 (3g`s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdeLGejYs